Cryopreservation of Abies alba embryogenic tissues by slow-freezing method - Salaj, Terezia; Panis, Bartholomeus; Klubicová, Katarina; Salaj, Jan (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2022)
Embryogenic tissues of Abies alba Mill. were cryopreserved using the slow-freezing approach. Four cell lines were incubated for 24 h on a medium with 0.5 M sorbitol and pre-treated with 5% DMSO. Subsequently, the tissues were frozen at a cooling rate of 1 °C min-1 to -40 °C and transferred to liquid nitrogen for 72 hours. After thawing in a water bath at 40 °C, the tissues were cultivated on a proliferation medium. All tested lines recovered, but variations in regrowth frequencies across cell lines were noticed (91.66 to 100%). The recovered tissues showed similar features to the control 2 (non-pre-treated and non-cryopreserved tissues). In the accumulation of fresh and dry mass, no statistically significant differences were observed between cryopreserved cultures and control 2. The cryopreserved tissues produced cotyledonary somatic embryos capable of germination. Microscopic observations revealed considerable structural changes as a consequence of the cryopreservation procedure. The long vacuolated suspensor cells were disrupted, and mostly the meristematic cells of the embryonal region survived. The typical bipolar structure of early somatic embryos has been regained during the post-thaw period. Differences in cryotolerance across cell lines were also observed.